Non-invasive therapies for management of temporomandibular disorders: A systematic review - Brochado, Fernanda Thomé; de Jesus, Luciano Henrique; Chaves, Karen Dantur; Martins, Manoela Domingues (Clinical and Biomedical Research, 2019)
Introduction: As a multifactorial disease, temporomandibular disorders (TMD) require a complex therapeutic approach, being noninvasive therapies the first option for most patients. The aim of this study was to perform a systematic review to analyze the most common non-invasive therapies used for TMD management. Methods: The review was done by searching electronic databases to identify controlled clinical trials related to pharmacologic and non-invasive treatments. Of all potential articles found, 35 were included in this review. Results: Low-level laser therapy (LLLT), occlusal splints (OS) and oral exercises/behavior education (OE/BE) were the most common therapies used. LLLT showed significant results in pain and movement improvement in most studies. OS was usually combined to other therapies and resulted in improvement of pain. OE/BE showed significant results when combined with ultrasound, LLLT, and manual therapy. Conclusions: Non-invasive treatments can provide pain relief and should be prescribed before surgical procedures. LLLT was the therapy with the higher number of studies showing positive results. Based in heterogeneity of treatment protocols, diagnostic and outcomes criteria used, new well-designed randomized controlled trials (RCT) are necessary. Keywords: Temporomandibular disorder; temporomandibular joint; myofascial pain; treatment; temporomandibular dysfunction; pharmacologic